2011
DOI: 10.1590/s0102-311x2011000300004
|View full text |Cite
|
Sign up to set email alerts
|

Aborto e coerção sexual: o contexto de vulnerabilidade entre mulheres jovens

Abstract: This study aims to investigate the relationship between abortion and experiences of sexual coercion. The data came from GRAVAD, a household survey with a stratified random sample of young women (18-24 years) IntroduçãoNo Brasil, o aborto destaca-se como um grave problema de saúde pública à medida que é amplamente praticado, muitas vezes de forma insegura, dentro de um cenário de clandestinidade 1 . A ilegalidade do aborto não coíbe a prática e perpetua as iniquidades socioeconômicas em que é realizado. Há, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 15 publications
2
25
0
8
Order By: Relevance
“…About this research, a survey exposed and discussed that abortion was being performed by women with high family income, which facilitated the occurrence because they had the resources to perform the practice. For these women, pregnancy was not desired and would hinder a professional future at that time [19]. If in the review articles the lack of financial conditions was considered one of the reasons for abortion, in this study of women of high purchasing power, the opposite is true, which is shown to be an agent that facilitates the act.…”
Section: Reasons That Led the Implementation Of The Act Of Abortionmentioning
confidence: 79%
See 1 more Smart Citation
“…About this research, a survey exposed and discussed that abortion was being performed by women with high family income, which facilitated the occurrence because they had the resources to perform the practice. For these women, pregnancy was not desired and would hinder a professional future at that time [19]. If in the review articles the lack of financial conditions was considered one of the reasons for abortion, in this study of women of high purchasing power, the opposite is true, which is shown to be an agent that facilitates the act.…”
Section: Reasons That Led the Implementation Of The Act Of Abortionmentioning
confidence: 79%
“…However, in all studies, pregnancy has always been undesirable. It is important that the nursing professional reflects about this entire socioeconomic context that involves women in situations of abortion, with an open look at change and totally free of preconceived judgments [19]. …”
Section: Reasons That Led the Implementation Of The Act Of Abortionmentioning
confidence: 99%
“…The lack of information on family planning and the lack of access to contraceptive methods contribute to the increase of these pregnancies and consequently to the increase of abortions in unsafe conditions (22)(23)(24)(25) . The decision to abort, often encouraged by the partner, shows that there was no planning carried out by the couple (22) .…”
Section: Semi-structured Questionnairementioning
confidence: 99%
“…Essa prática na adolescência representa 7% a 9% do total de abortos provocados no Brasil, e 72,5% a 78% deles ocorrem na faixa etária de 17 a 19 anos, revelando maiores chances de sua ocorrência à medida que a idade diminui (PILECCO; KNAUTH; VIGO, 2011).…”
Section: Introductionunclassified